SME's PERFORMANCE DAN PRODUCT INNOVATION PADA UMKM KULINER DI KABUPATEN KUDUS: PENGARUH TRANSFORMATIONAL LEADERSHIP DAN ENTREPRENEUR ORIENTATION - Fahira, Keke Tamara; Faidah, Faridhatun; Rusdianto, Hutomo; Nugroho, Dennyca Hendriyanto (KEUNIS, 2024)
The aims this research to test of transformational leadership and entrepreneurial orientation on SME's Performance through product innovation. Small and Medium Enterprises are one of the pillars and strengths that contribute to the Indonesian economy. The number of MSMEs in Kudus Regency is the lowest among the surrounding cities, only 990 MSMEs. MSMEs must be able to navigate changes in their business environment, which requires leaders who can take appropriate action. It is necessary to apply leadership styles, such as transformational leadership and innovate to improve the performance of MSMEs. Through Product Innovation and Entrepreneur Orientation, then MSMEs can keep up with developments in the era so they can present superior products that have a greater chance of attracting consumers. Data analysis uses the AMOS Structural Equation Model (SEM) using validity tests, reliability tests, classical assumption tests which include confirmatory factor analysis normality tests, full measurement models, hypothesis tests and intervening tests. The results of this research are that transformational leadership and entrepreneurial orientation have a significant positive effect on SME's Performance. However, transformational leadership and entrepreneurial orientation have an insignificant positive effect on product innovation. Product innovation is able to partially mediate transformational leadership and entrepreneurial orientation on SME's Performance.